Incentivizing creativity: A large-scale experiment with tournaments and gifts - Christiane Bradler; Susanne Neckermann; Arne Jonas Warnke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper reports the results from a large-scale laboratory experiment investigating the impact of tournament incentives and wage gifts on creativity. We find that tournaments substantially increase creative output, with no evidence for crowding out of intrinsic motivation. By comparison, wage gifts are ineffective. Additional treatments show that it is the uncertain mapping between effort and output that inhibits reciprocity. This uncertainty is prevalent in creative and other complex tasks. Our findings provide a rationale for the frequent use of tournaments when seeking to motivate creative output.
Keywords: C91; D03; J33; M52; 330; creativity; incentives; tournament; reciprocity; experiment; crowding-out